Early magnetic resonance imaging to detect presymptomatic leptomeningeal angioma in children with suspected Sturge–Weber syndrome. (3rd May 2019) - Bar, Claire; Pedespan, Jean‐Michel; Boccara, Olivia; Garcelon, Nicolas; Levy, Raphael; Grévent, David; Boddaert, Nathalie; Nabbout, Rima
Abstract : Aim: We aimed to evaluate the contribution of early magnetic resonance imaging (MRI) for the presymptomatic diagnosis of Sturge–Weber syndrome (SWS) in infants with a facial port‐wine birthmark (PWB). Method: Asymptomatic infants with a facial PWB who performed a first MRI scan before 3 months and a second MRI scan after 9 months were included in this study. Leptomeningeal enhancement on T1‐weighted imaging and four indirect signs of leptomeningeal angioma (choroid plexus enlargement, cerebral atrophy, signal inversion of the white matter with T2 hyposignal, and T1 hypersignal) were screened on the first MRI scan and correlated with clinical and/or radiological diagnosis of SWS. Results: Thirteen of 30 included patients had SWS with leptomeningeal angioma. Eleven had a leptomeningeal enhancement on the first MRI scan and 10 had associated indirect signs. The presence of a direct or at least one indirect sign of leptomeningeal angioma on the first MRI scan confirmed the diagnosis of SWS with a sensitivity of 100 per cent (95% confidence interval 75–100%) and a specificity of 94 per cent (71–100%). Interpretation: Early diagnosis of SWS is possible on contrast‐enhanced MRI performed in asymptomatic infants with a facial PWB before the age of 3 months. This early detection would help to select patients who may benefit from early neuroprotective intervention. What this paper adds: Specific magnetic resonance imaging markers provide early diagnosis of leptomeningeal angioma in Sturge–Weber syndrome (SWS). Presymptomatic diagnosis of SWS should help to select patients for early therapy intervention. What this paper adds: Specific magnetic resonance imaging markers provide early diagnosis of leptomeningeal angioma in Sturge–Weber syndrome (SWS). Presymptomatic diagnosis of SWS should help to select patients for early therapy intervention.